Involvement of Heat Shock Protein A4/Apg-2 in Refractory Inflammatory Bowel Disease. Issue 1 (January 2015) - Adachi, Teppei; Sakurai, Toshiharu; Kashida, Hiroshi; Mine, Hiromasa; Hagiwara, Satoru; Matsui, Shigenaga; Yoshida, Koji; Nishida, Naoshi; Watanabe, Tomohiro; Itoh, Katsuhiko; Fujita, Jun; Kudo, Masatoshi
Abstract : Background: Expression of heat shock protein A4 (HSPA4, also called Apg-2), a member of the HSP110 family, is induced by several forms of stress. The physiological and pathological functions of HSPA4 in the intestine remain to be elucidated. Methods: We assessed HSPA4 expression and function by generating HSPA4-deficient mice and using 214 human intestinal mucosa samples from patients with inflammatory bowel disease (IBD). Results: In the colonic mucosa of patients with IBD, a significant correlation was observed between the expression of HSPA4 and antiapoptotic protein Bcl-2, a T-cell–derived cytokine IL-17 or stem cell markers, such as Sox2. In refractory ulcerative colitis, a condition associated with increased cancer risk, expression of HSPA4 and Bcl-2 was increased in inflammatory cells of colonic mucosae. HSPA4 was overexpressed both in cancer cells and immune cells of human colorectal cancers. Patients with high expression of HSPA4 or Bmi1 showed significantly lower response rates upon subsequent steroid therapy as compared with patients with low expression of each gene. HSPA4-deficient mice exhibit more apoptosis and less expression of IL-17/IL-23 in inflammatory cells and less number of Sox2 + cells after administration of dextran sodium sulfate than control mice. Transduction of HspaA4 +/− bone marrow into wild-type mice reduced the immune response. Conclusions: Upregulation of Bcl-2 and IL-17 by HSPA4 would control apoptosis of inflammatory cells and immune response in the gut, which might develop treatment resistance in IBD. HSPA4 and Bmi1 would be a useful biomarker for refractory clinical course and a promising approach for a therapeutic strategy in patients with IBD. Abstract : Article first published online 1 December 2014.Supplemental Digital Content is Available in the Text.